Together we are better: analysis of coproduction in public educational services in schools of Campina Grande/PB - Guimarães, Gilson Pereira (2023)
Coproduction is a governmental strategy aimed at involving civil society in improving public services, particularly relevant in the field of education. This study aims to analyze coproduction in public education services in schools in Campina Grande/PB. The research adopted a qualitative approach through interviews with administrators, teachers, students, and parents. Several examples of co-production were found, such as the implementation of democratic budgets, the adoption of participatory councils, and the collaboration of various actors in society to enhance student education. It was observed that the municipal elementary school demonstrated a greater diversity of examples, partnerships, and strength in coproduction compared to the state high school.